INDIVIDUAL BLOOD DIFFERENCES IN MEXICAN INDIANS WITH SPECIAL REFERENCE TO THE RH BLOOD TYPES AND HR FACTOR - ZEPEDA, JP; WIENER, AS; SONN, E B; POLIVKA, H R (OFFICE OF CHIEF MED EXAMINER, NEW YORK, NY, EUA, 1950)
98 Mexican Indians were tested for the blood properties A-B-O, A1-A2, M-N, P, Rh'-Rh''-Rh0-rh, and Hr. Of the 98 Indians, 90.8 per cent belonged to group 0, 6.1 per cent belonged to A1, and 3.1 per cent to group B. There were 61.2 per cent of type M, 3.1
J EXP MED
Keywords: DIFFERENCES, MEXICAN- INDIANS, BLOOD, TYPES, FACTOR- RH; CIENCIAS MEDICAS; OTRAS ESPECIALIDADES MEDICAS (ESPECIFICAR); MEDICINA BIOQUIMICA